Undang-Undang ITE: Sang Tombak atau Tameng Dunia Maya - Fandy Kusuma Faizal (Jurnal Litigasi Amsir, 2022)
This research aims to determine the development of Information and Communication Technology, factors for the needs and targets of the use of information technology, and the causes of the emergence of rampant issues related to the ITE Law. This research method uses empirical normative research. The results showed that the public already knew the ITE Law, but had not been able to interpret the ITE Law correctly. The lack of socialization and literacy related to the ITE Law so has not been able to distinguish which victims are the perpetrators of violations of the Law. Therefore, let’s be wiser in using this increasingly sophisticated information technology. Make the most of it for good and right things, so that no one reports each other anymore using the ITE Act and no one feels disadvantaged by this ITE Act anymore.